Characteristics, Perspectives, and Experiences of Cyproheptadine Users at Community Pharmacies in the Context to Prescription Medication Misuse - Alssageer, Mustafa; Ali Alsahref,; Mokter Abdelqader, (AlQalam Journal of Medical and Applied Sciences, 2024)
Some people abuse the antihistamine medication cyproheptadine in an attempt to reach their desired shape, weight, and appearance. This study aims to investigate the characteristics of cyproheptadine misusers as well as their behaviors, perceptions, experiences, and sources of information regarding using this medication. A descriptive cross-sectional study was carried out in Sebha City among customers of community pharmacies. Each customer who has taken cyproheptadine was invited to participate in this research. The data was collected from April 2022 until September 2022. Almost all of the participants (n=99, 96.1%) reported they purchased cyproheptadine from community pharmacies and obtained the drug without a prescription n=79 (76.7%). Over half of the respondents (n=53, 51.5%) use this drug for increasing appetite, compared to (n=25,24.3%) and (n=19, 18.4%) respondents who said they used it to improve their shape and lose weight, respectively. Most participants indicated they were unaware of other uses of a drug (n=72, 69.9%) or its side effects (n=61, 59.2%). Furthermore, twenty participants (19.4%) denied receiving information concerning the precautions and contraindications of using cyproheptadine. The highest rate of source of drug information reported by participants was “friends or family member” (n=34, 33%) followed by pharmacists (n=29, 28.2%). Community pharmacies must employ qualified pharmacists on staff to give customers trustworthy information regarding prescription pharmaceuticals such as cyproheptadine. يسيء بعض الأشخاص استخدام عقار السيبروهيبتادين المضاد للهيستامين في محاولة للوصول إلى الشكل والوزن والمظهر المرغوبين. تهدف هذه الدراسة إلى التحقيق في خصائص مستخدمي السيبروهيبتادين بالإضافة إلى سلوكياتهم وإدراكاتهم وتجاربهم ومصادر المعلومات المتعلقة باستخدام هذا الدواء. أجريت دراسة مقطعية وصفية في مدينة سبها بين عملاء الصيدليات المجتمعية. تمت دعوة كل عميل تناول السيبروهيبتادين للمشاركة في هذا البحث. تم جمع البيانات من أبريل 2022 حتى سبتمبر 2022. أفاد جميع المشاركين تقريبًا (ن = 99، 96.1٪) أنهم اشتروا السيبروهيبتادين من الصيدليات المجتمعية وحصلوا على الدواء بدون وصفة طبية ن = 79 (76.7٪). أكثر من نصف المشاركين (ن = 53، 51.5٪) يستخدمون هذا الدواء لزيادة الشهية، مقارنة بـ (ن = 25، 24.3٪) و (ن = 19، 18.4٪) من المشاركين الذين قالوا إنهم يستخدمونه لتحسين شكلهم وفقدان الوزن، على التوالي. أشار معظم المشاركين إلى أنهم لم يكونوا على علم باستخدامات أخرى للدواء (ن = 72، 69.9٪) أو آثاره الجانبية (ن = 61، 59.2٪). وعلاوة على ذلك، نفى عشرون مشاركًا (19.4٪) تلقي معلومات تتعلق بالاحتياطات وموانع استخدام سيبروهيبتادين. وكان أعلى معدل لمصدر معلومات الدواء الذي أبلغ عنه المشاركون هو "الأصدقاء أو أحد أفراد الأسرة" (ن = 34، 33٪) يليه الصيادلة (ن = 29، 28.2٪). يجب على الصيدليات المجتمعية توظيف صيادلة مؤهلين على الموظفين لإعطاء العملاء معلومات جديرة بالثقة فيما يتعلق بالأدوية الموصوفة مثل سيبروهيبتادين